2021
DOI: 10.1038/s41598-021-89354-6
|View full text |Cite
|
Sign up to set email alerts
|

3-D health trajectories and related childhood predictors among older adults in China

Abstract: This study aimed to identify the multi-trajectories of 3-D health of older adults in China and to explore whether the childhood predictors are associated with 3-D health trajectory. Data came from five waves of the China Health and Retirement Longitudinal Study (CHARLS, 2011 to 2018). A multi-trajectory modeling approach was carried out to jointly estimate the trajectories of 3-D health. A multinomial regression model was used to investigate the relationships between childhood predictors and the joint trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, few studies examined how childhood experiences influenced the baseline level and change rate of frailty in the context of developing countries and regions such as China. Empirical studies in China have found partial evidence of the associations between the three childhood antecedents and trajectories of cognition, depression, and disease in later life (Pan et al 2021 ; Yang and Wang 2020 ). Given that these symptoms are important components of frailty, we suspect that experiences in childhood might also have long-term influences on frailty trajectory among Chinese middle-aged and older adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies examined how childhood experiences influenced the baseline level and change rate of frailty in the context of developing countries and regions such as China. Empirical studies in China have found partial evidence of the associations between the three childhood antecedents and trajectories of cognition, depression, and disease in later life (Pan et al 2021 ; Yang and Wang 2020 ). Given that these symptoms are important components of frailty, we suspect that experiences in childhood might also have long-term influences on frailty trajectory among Chinese middle-aged and older adults.…”
Section: Introductionmentioning
confidence: 99%